Brand Equity for Tablet Chocolate and Convenience Product Purchases by Women - Bozkurt, Bilgehan (British Journal of Marketing Studies, 2016)
This research aims to demonstrate direct influences of marketing mix variations on the customer-based brand equity process for tablet chocolate and convenience products. The proposed model examines product quality, price perception, reaction to stock-outs, the perceived effect of advertising as antecedents of the customer-based brand equity process, along with the moderation of brand consciousness. Methodology includes simple random sampling and the partial least squares. Sample involves 172 female tablet chocolate consumers out of Generation X and Millennials in Istanbul, Turkey. Results indicate that product quality generates brand knowledge and loyalty, but price perception generates only loyalty. Besides, brand consciousness moderates the effect of product quality on brand knowledge. Implications include the effects of neglecting brand experience, the link between operations and marketing, and transition of marketing mix. The final model is proposed as a minimum requirement to substitute tablet chocolate branding due to concerns about public health and sugar consumption.